The impact of farmer partnerships on arabica coffee farming in Simalungun Regency, North Sumatra Province, Indonesia - Linda Tri Wira Astuti; Diana Sofia Huitron Flores; Iman Arman; Herawati Herawati; Yenny Laura Butarbutar (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2022)
Coffee is one of Indonesia's main economic activities for foreign exchange. An increase in exports of 8.11%, and a decline in imports of 58% in 2019, opened up export opportunities and large domestic markets. The government has implemented efforts to improve coffee farmers' welfare, one of which is agricultural business partnerships that can solve smallholder problems in developing countries and expand subsistence or traditional agriculture to high production value and export-oriented. This research aimed to analyze (1) the factors influencing coffee farmers' participation in agricultural partnerships and (2) the impact of the agricultural partnership on coffee farmers' performance in Simalungun Regency, North Sumatra Province. The Propensity Score Matching (PSM) technique analyzed the partnership's influence on coffee farming and agricultural income, productivity, and prices. The results showed that number of dependents household members and land area influence farmers' partnership participation. Participation increases coffee farming and agricultural income, productivity, and prices.